2005
DOI: 10.1128/mcb.25.9.3630-3638.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidylinositol 3-Phosphate Phosphatase Myotubularin- Related Protein 6 (MTMR6) Is a Negative Regulator of the Ca2+-Activated K+ Channel KCa3.1

Abstract: Myotubularins (MTMs) belong to a large subfamily of phosphatases that dephosphorylate the 3 position of phosphatidylinositol 3-phosphate [PI(3)P] and PI(3,5)P 2 . MTM1 is mutated in X-linked myotubular myopathy, and MTMR2 and MTMR13 are mutated in Charcot-Marie-Tooth syndrome. However, little is known about the general mechanism(s) whereby MTMs are regulated or the specific biological processes regulated by the different MTMs. We identified a Ca 2؉ -activated K channel, K Ca 3.1 (also known as KCa4, IKCa1, hIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 43 publications
4
104
0
Order By: Relevance
“…For instance, mice deficient for mitsugumin-29 display similar ultrastructural abnormalities, but only minor defects in muscle strength (37). Myotubularin activity on PI(3)P and/or PI(3,5)P 2 could also play a direct role on channel activation, as previously reported for a homologous protein, MTMR6, which regulates the activity of the Ca 2ϩ -activated K ϩ channel KCa3.1 via PI(3)P (38,39). Other mutant mice with deletions in genes involved in triad formation and/or calcium homeostasis, such as junctophilin 1 and triadin, also contain muscles with abnormally oriented T-tubules and alterations in Ca 2ϩ transients and/or E-C coupling (40) (41).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, mice deficient for mitsugumin-29 display similar ultrastructural abnormalities, but only minor defects in muscle strength (37). Myotubularin activity on PI(3)P and/or PI(3,5)P 2 could also play a direct role on channel activation, as previously reported for a homologous protein, MTMR6, which regulates the activity of the Ca 2ϩ -activated K ϩ channel KCa3.1 via PI(3)P (38,39). Other mutant mice with deletions in genes involved in triad formation and/or calcium homeostasis, such as junctophilin 1 and triadin, also contain muscles with abnormally oriented T-tubules and alterations in Ca 2ϩ transients and/or E-C coupling (40) (41).…”
Section: Discussionmentioning
confidence: 53%
“…Thus, Ca 2+ release from the sarcolemma is initiated by excitation. Additionally, local PI homeostasis of PI(3)P and PI(3,5)P 2 , controlled by myotubularins, was shown to regulate ion channel activity (Srivastava, Li et al 2005;Shen, Yu et al 2009). Defective membrane organization and channel activity might have additive effects on muscle dysfunction, reflected by the severe form of myotubular myopathy.…”
Section: Common Features Of Mtm1 Deficiency Cause Xlcnm Pathologiesmentioning
confidence: 99%
“…Together, these findings suggest that macropinocytosis is controlled by the sequential breakdown of PI(3,4,5)P 3 → PI(3,4)P 2 → PI(3)P → PI in the PM. Furthermore, we showed that KCa3.1, a Ca 2+ -activated K + channel that is activated by a PI(3)P (26)(27)(28), is essential for macropinocytosis.…”
Section: Significancementioning
confidence: 99%